A 6‐node triangular solid‐shell element for linear and nonlinear analysis. (7th February 2017) - Ko, Yeongbin; Lee, Phill‐Seung
Summary: In this paper, we present an effective 6‐node triangular solid‐shell element (MITC‐S6), with particular attention on shear locking and thickness locking. To alleviate shear locking, the assumed transverse strain field of the MITC3+ shell element is used while modifying the bending enhancement mechanism. Thickness locking is treated using the assumed and enhanced strain methods for thickness strain. Two independent enhancements of strains are applied: The in‐plane and transverse shear strain fields are enhanced using the strain fields obtained from a bubble interpolation function for in‐plane translations, and the thickness strain field is enhanced for linear variation in the thickness direction. The general three‐dimensional material law is employed. The proposed element passes all the basic tests including zero‐energy mode, patch, and isotropy tests. Excellent performance is observed in various linear and nonlinear benchmark tests, wherein its performance is compared with that of existing 6‐node triangular and 8‐node quadrilateral solid‐shell elements. Copyright © 2016 John Wiley & Sons, Ltd.